COVID-19 and Orthopaedics: Recovery After the Pandemic Surge - Brandon Petrone, D.O; Cesar R. Iturriaga, D.O; Thomas Mauri, M.D; Nicholas Sgaglione, M.D (Elsevier, 2020)
The novel Coronavirus (COVID-19) pandemic has placed an immense strain on health care systems and orthopedic surgeons across the world. To limit the spread, federal and state governments mandated the cancellation of all nonurgent surgical cases to address surging hospital admissions and manage workforce and resource reallocation. During the pandemic surge, thousands of surgical cancellations have been required. We outline our experience through the onset and advance of the surge, detail our incident response and discuss the transition toward recovery. Level of Evidence: Level V